The changing dynamics of HIV/AIDS during the Covid-19 pandemic in the Rohingya refugee camps in Bangladesh - a call for action - Muhammad Anwar Hossain; Iryna Zablotska-Manos (University of New South Wales, 2022)
The COVID-19 pandemic has affected every country's health service and plunged refugees into the most desperate conditions. The plight of Rohingya refugees is among the harshest. COVID-19 has severely affected their existing HIV/STI prevention and management services and further increased the risk of violence and onward HIV transmission within the camps. In this commentary, we discuss the context and the changing dynamics of HIV/AIDS during COVID-19 pandemic, among the Rohingya refugee community in Bangladesh. What we currently observe is the worst crisis in the Rohingya refugee camps thus far. Because of being displaced, Rohingya refugees have increased vulnerability to HIV, STIs and other poor health outcomes. They have inadequate access to HIV testing, treatment, and care. Their host country has poor capacity to provide services. Complex economic, socio-cultural and behavioural factors exacerbate their poor access to HIV testing, treatment, and care. The unfolding COVID-19 pandemic has changed priorities in the Rohingya refugee camps so that more emphasis is being placed on COVID-19 prevention and treatment rather than other health issues. This exacerbates the already dire situation with HIV detection, management, and prevention among the refugees. Although the government of Bangladesh and different non-governmental organisations provide harm reduction, HIV care, and COVID-19 care to refugees, a comprehensive response is needed to maintain and strengthen health programs for refugees, for both HIV and COVID-19 care. This comprehensive response should include behavioural intervention, community mobilisation, and effective treatment and care. Without addressing the disadvantage of social conditions, it will be challenging to reduce the burden of HIV and COVID-19 among refugees. While the COVID-19 crisis is a global challenge, the international community has an obligation to improve the life, livelihood and health of those who are most vulnerable. Rohingya refugees are among them.